Fertilization and development of mice (Mus musculus) embryo in vitro after supplementing the extract of Pandanus conoideus - KARTINI ERIANI; PUTRI LAILAN TIFANI; SYAHRUDDIN SAID (Smujo International, 2017)
Eriani K, Tifani PL, Said S. 2017. Fertilization and development of mice (Mus musculus) embryo in vitro after supplementing the extract of Pandanus conoideus. Nusantara Bioscience 9: 202-208. An extract of red fruit (ERF/Pandanus conoideus Lam.) contains beta-carotene and alpha-tocopherol, i.e. antioxidant compounds group which can stop the formation of free radicals during in vitro fertilization. Reactive oxygen species (ROS) is a free radical which resulted in an oxygen derivate. This research aimed to determine the effect of ERF supplementation on fertilization rate and embryo in vitro development of mice. The study used Completely Randomized Design (CRD) with three group of treatments (ERF dosage supplement: 0 mL, 0.05 mL, and 0.1 mL) and three replications. Each dosage was added to five mice in 7 days. In total, 45 samples were used. Research procedure included extraction of P. conoideus Lam, treatment on the sample, superovulation, preparation of sperm, oocyte collection, in vitro fertilization, and in vitro culture. Parameters observed were the quality of oocyte, the fertilization rate of mice and the development stage of in vitro pre-implantation mice embryo. Acquired data analyzed quantitatively using One Way ANAVA and Duncan’s Multiple Range Test (DMRT) at 5% significance level. The result showed that all treatments did not affect significantly (p>0.05) on the quality of oocyte, in vitro fertilization of oocyte and in vitro early development of embryo. Suggested for further research about the improvement technique of in vitro fertilization and early embryo development.